Populist Foreign Policy and Mobilization in Bolivia - Plagemann, Johannes; Heras Rodríguez, Carlos; Destradi, Sandra (Política. Revista de Ciencia Política, 2022)
The goal of this article is to explore the role of mobilization in the foreign policies of populists in power. To do so, we focus on the main features and changes of Bolivia’s foreign Policy under its populist president Evo Morales (2006-2019) with regard to its two most prominent conflictive bilateral relations, with the US and Chile. In both domains, Morales departed from the foreign policy of previous governments. By ending cooperation with the US, the Morales government sought to establish a sovereign counternarcotics policy in line with its core constituency’s demands of legalizing coca crops. On the key issue of relations with Chile seeking to negotiate a sovereign access to the Pacific Ocean, the Morales government exhibited more continuity initially. However, by referring the stalemated conflict to the International Court of Justice, Morales eventually changed his country’s approach to finding a resolution. Tracing Morales’ discourse over time reveals an intensification of populist as well as hostile rhetoric in periods of domestic political instability. Thus, our findings support the theoretical expectation of a particularly close link between domestic politics and foreign policy under populists in power. Thereby, populism may lead to a more conflictive foreign policy in some cases. However, neither does populist mobilization over foreign policy matters necessarily drive foreign policy change, nor does it preclude genuine bilateral dialogue.